Konsep Pendidikan Multiple Intelligences Dan Relevansinya Terhadap Pendidikan Islam - Sri Wulan (Departement of Mathematics Education, 2023)
The concept he called Multiple Intelligence.Based on this, the writer formulates the problem formulation as follows: 1) What is the concept of Multiple Intelligence in The Classroom according to Thomas Armstrong?. 2) How is intelligence according to the Islamic perspective?. 3) How is the relevance of the concept of Multiple Intelligence in the Classroom according to Thomas Armstrong with the concept of contemporary Islamic education?. In accordance with the formulation of the problem stated above, the objectives of this study are to: 1) Understand the concept of Multiple Intelligence in the Classroom according to Thomas Armstrong. 2) Understanding intelligence according to Islamic perspective. 3) Get an overview of the relevance of the concept of Multiple Intelligence in The Classroom according to Thomas Armstrong with the concept of contemporary Islamic education.This research is a type of qualitative research. The author looks for library information through reading scientific journals, reference books, relevant scientific works and various actual research results. Then the researcher describes the concept of intelligence according to Thimas Armstrong, intelligence according to Islam and the relevance of intelligence according to Thomas Armstrong with the concept of contemporary Islamic educationAfter analyzing various literatures and reflecting on Thomas Armstrong's Multiple Intelligence thinking and the concept of intelligence according to Islam, the authors conclude that: 1) Armstrong's intelligence consists of linguistic, logical mathematical, spatial, kinesthetic, musical, interpersonal, intrapersonal and natural intelligence. 2) Islam views that intelligence consists of intellectual, emotional and spiritual intelligence. 3) Linguistic, logical mathematical and spatial intelligence is relevant to intellectual intelligence according to Islam. Meanwhile, kinesthetic, musical, interpersonal and intra-personal intelligence are in accordance with emotional intelligence. The author adds existential intelligence and categorizes it as spiritual intelligence along with natural intelligence.